Influência materna nas caracteristicas morfológicas de ovários e testículos de fetos bovinos da raça Nelore - Souza, Juliana Stephani de [UNESP] (2014)
The study of gonadal development allows to understand some factores that can interfere in its development and futurely, in animal reproductive profile, in adult life. Considering the cows body condition and physiological influences on the development of fetal organs during the pregnancy, This experiment aimed to evaluate the fetal testicular and ovarian morphological development in beef cattle of Nelore breed and compare it to maternal body condition (carcass weight - CW, carcass yield grade - CYG, age and antral follicle counts - ACF). There were collected 372 bovines fetus from Nellore cows (210 females and 162 males), aging between 3 and 8 months, obtained from a slaughterhouse in Araçatuba region - SP. Blood samples from the cows were collected to leptin, insulin and progesterone plasmatic quantification. The gonadal weight (g) and volume (mm³) were measured. The fetal gonads were submitted to classical histology proceedings and 3 μm thickness were cut, in 210 μm intervals. During gestation, both fetus ovarian weight and volume were correlated with the number of ovarian follicles (NOF) (r=0,78, p<0,0001 and r=0,80, p<0,0001) and in male, both testicular weight and volume were correlated with Sertoli cells count (CS; r=0,84, p<0,0001 and r=0,92, p<0,0001), Leydig cells count (LC; r=0,80, p<0,0001 and r=0,90, p<0,0001) and germ cells count (GC; r=0,84, p=<0,0001 and r=0,93, p<0,0001). Maternal age was correlated with primary follicles count (r=0,14, p=0,05) in the fetal ovaries...(Complet4 abstract click eletronic acess below)